Decoupling the environmental impacts of transport from economic growth - Organisation for Economic Co-operation and Development (Paris : OECD, 2006)
Transport activity continues to cause large adverse impacts on the environment, human health and the economy. But is a negative impact of transport on the environment a necessary consequence of economic growth? This book illustrates that decoupling the environmental impacts of transport from economic growth is achievable, through the efficient use of charges, fees, taxes and other economic instruments. These economic approaches can complement regulatory measures to encourage a shift towards more environmentally-friendly modes of transport, such as from road to certain forms of rail transport. Other factors which could help to decouple transport impacts from economic growth are improvements in freight transport logistics, and dematerialization.--Publisher's description
Transport and the economy -- Transport and the environment -- Decoupling indicators -- Policy instruments for decoupling -- National case studies -- Conclusion : towards a decoupling strategy
Includes bibliographical references
Keywords: Transportation -- Environmental aspects; Economic development